Analisis Penerapan Sanksi Terhadap Wanprestasi Nasabah Pada Akad Murabahah di BMT Amanah Ummah Cabang Sukoharjo (Studi Atas Kesesuaian Fatwa Dewan Syariah Nasional) - Ridoh, Muhammad Rasyid, Dr. M. Muhtarom, SH. MH (2016)
Murābahah transaction is similar to business characteristics (tijārah) because it can make benefit (profit) and also, it can be risky (loss) that must be anticipated. One of the risks is a failure to obey agreement (default) in part of client. In order to anticipate losses elicited by the failure, then penalties were assigned to the default clients in sharia financial institutions and conventional ones of Indonesia. In addition, penalties cannot be assigned arbitrarily without considering justice elements as stated in Al-Qur'an and Sunnah and laws of Indonesian Republic. BMT Amanah Ummah of Sukoharjo branch is one of sharia financial institution that is applying penalties in Murābahah transaction to default clients. As an Islamic-based financial institution, BMT Amanah Ummah is, of course, making instructions published by National Sharia Council as one of guides in its every activity. Purpose of the research is to know conformity of penalties application to clients who are failed to obey Murābahah agreement in BMT Amanah Ummah of Sukoharjo branch based on instruction of National Sharia Council, especially about fine penalty. In order to understand the problem, researcher used field research with descriptive-qualitative method, namely a method of describing occurrence or facts found in field, then researcher evaluated penalties implementation in BMT Amanah Ummah of Sukoharjo branch based on instructions of National Sharia Council and supported by results of interview and documentation. Based on the research, it can be concluded that based on data presentation and revealing of Murābahah transactions, implementation of penalties by BMT Amanah Ummah of Sukoharho branch was agreeing with content of instructions published by National Sharia Council. Fine penalties applied by the Islamic bank were allowed by instruction of National Sharia Council, namely DSN No. 17/DSN/IX/2000 and money of the penalties that were distributed by the bank to LAZIS UMS was conforming to contents of the instruction requiring that the fund obtained from penalties should be provided to social fund. Penalty of security goods auction was also agreeing with content of instruction of DSN No. 47/DSN-MUI/II/2005 in which the Islamic bank can sell Murābahah object/security goods, and if money acquired from the auction exceeds obligation of the client, the excess will be returned to client, whereas if the money is less than obligation of the client, then the shortage will still be obligation of the client. Key words: Penalty, Failure to obey Agreement, Murabahah, BMT Amanah Ummah, Instruction of National Sharia Council